The Search for Heritage in Ottawa's Lower Town - Newton, Michael (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
Few buildings survive the first generation (approx. 1826-1850) of urban growth in the Lower Town portion of present-day Ottawa, even though most of the commercial activity and population was concentrated there. Most are unprepossessing, as is much of the contemporary area. An explanation lies in the determination of Governor Dalhousie and the British Board of Ordnance — builders of the Rideau Canal — to plan and control the embryonic townsite through land leasing. The British Board of Ordnance owned, outright, about half the land in early Bytown, including all of Lower Town. Prospective builders were leased town lots, usually on a 30-year basis. Legitimate builders were thus reluctant to invest in substantial structures, as were speculative builders, constructing instead temporary, ramshackled edifices. The first buildings of substance date from the latter 1840s when conversion to freehold became possible. The option of leasehold persisted, however, until at least the 1870s, and the mixture of tenures sustained the impulse for temporary structures. In the case of Lower Town, proprietal relationships were fundamental in the evolution of the urban landscape.